The research of Tuna Huichun Gong on pulmonary function, exercise tolerance, and quality of life in patients with chronic obstructive pulmonary disease based on the concept of early pulmonary rehabilitation - Yu, Wei (Medicine (Baltimore), 2020)
INTRODUCTION: Chronic obstructive pulmonary disease (COPD) is a common high-burden and highly disabling lung disease. The quality of life and exercise endurance of patients with COPD is often low because of atrophy of the respiratory and skeletal muscles. Although recommended by the global initiative for chronic obstructive lung disease guidelines, pulmonary rehabilitation (PR) has not been used widely because of its inherent limitations. Tuna-Hui-Chun-Gong (TNHCG) is a popular traditional exercise used to treat COPD in China. We aim to evaluate the safety and efficacy of TNHCG for PR of COPD. METHODS: The provided protocol is for a single-blind randomized controlled trial in which 120 COPD patients will be randomly and equally divided into the experimental or control group. The control group will be treated with standard COPD drugs while the experimental group will perform TNHCG exercises apart from standard drug treatment. The duration of treatment will be 24 weeks and a follow-up for 48 weeks. The primary outcome will be the 6-Minute Walk Test. The secondary outcomes will include the pulmonary function test, St George's respiratory questionnaire, COPD assessment test, modified medical research council dyspnea scale, Hospital Anxiety and Depression Scale, and exacerbation frequency. A safety assessment will also be performed during the trial. DISCUSSION: Our study will provide evidence to support TNHCG exercise as an additional measure for PR of COPD. TRIAL REGISTRATION: ChiCTR1900028332, Registered December 29, 2019. ETHICS AND DISSEMINATION: Ethics approval has been granted by the Sichuan Traditional Chinese Medicine Regional Ethics Review Committee (No. 2019KL-050).